The minimal caloric test asymmetric response in vertigo-free migraine patients - Maranhão, Eliana Teixeira; Maranhão, Péricles, Filho; Vincent, Maurice Borges; Luiz, Ronir Raggio (Arquivos de Neuro-Psiquiatria, 2016)
Vertigo symptoms and subclinical vestibular dysfunctions may occur in migraine. The Minimal Caloric Test (MCT), an easy-to-perform, convenient and yet informative procedure was used to test the vestibular function in 30 vertigo-free migraine patients outside attacks and 30 paired controls. Although not statistically significant, a right-to-left nystagmus duration asymmetry greater than 25% was present in both groups. This difference was greater in the patients group, suggesting the presence of subclinical vestibular imbalance in migraine.
Keywords: migraine; vestibular system; minimal caloric test